Rule school - Quigley, Dawn (Quigley, Dawn. Jo Jo Makoons, 2024)
"Jo Jo and her classmates are excited that the Elders' Tribal Center has changed the rules for the talent show to invite the whole tribe to perform. But the rules have also changed in Jo Jo's classroom, where instead of their teacher, they have a substitute. Since Jo Jo has a knack for being helpful, she puts her mind to helping her classmates decide on their talents--but can she manage to follow the substitute teacher's rules? Even if no one else quite understands Jo Jo's own rules . . . her undeniable talent for celebrating, curiosity, and class keep her happily hop-skipping in step with her Ojibwe community"--OCLC.